O sistema de gestão de segurança e saúde dos trabalhadores: estudo de caso em uma indústria petroquímica no Rio de Janeiro - Almeida, Telma Canela Miranda de (2003)
The present dissertation is based on investigation related to strategies used for the Safety and I-Iealth Management System in petrochemical industries, specially Petroflex. The objective is to analyse procedures for the industry in reference, used to assure the safety and health of workers envolved on production, specially on areas where risk activities are involved. The ressearch s result is now presented, not only the point where there is innovation and correct attitudes; it also suggests operational changes to assure the workers integrity. In this case, the dissertation can work as a bibliography reference and can also be useful for petrochemical industries and others to proceed to minimize the accidents risks.